Effect of Giving Oxygen Therapy Using Non-Breathing Mask on Changes in Intraparsial Pressure Value in Head Injury Patients at Home Grandmed Hurt of Lubuk Pakam - Raynald Ignasius Ginting; Putri Sari Fadilla Sitorus (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Objective: Head injury is a traumatic disturbance of brain function accompanied or without brain bleeding with a sudden blow or impact to the head without loss of consciousness. Oxygen is a gas component and a vital element in metabolic processes to maintain the viability of all body cells normally by inhale the room air with each breath. Knowing the value of intrapartial pressure by administering non-breathing mask oxygen with differences in intrapartial pressure values ??in head injured patients at Grandmed Lubuk Pakam Hospital. The research method used a purposive sampling technique with a total sample of 21 respondents, while the research instrument used an observation sheet with an oximetry measuring instrument. Data analysis used bivariate analysis, namely the Paired Sample T-Test. Results; The results of the Bivariate test with the Paired Sample T-Test proved that there was an effect of giving non-breathing mask oxygen therapy on intrapartial pressure values ??in head injured patients as evidenced by the p value: 0.00 <0.05. Conclusion; There is an effect of giving threapy oxygen using a non-breathing mask on changes in intrapartial pressure values ??in head injured patients at Grandmed Lubuk Pakam Hospital.